2008
DOI: 10.1002/bio.1049
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of surfactant‐sensitized chemiluminescence of bis(2,4,6‐trichlorophyenyl) oxalate and hydrogen peroxide induced by gold nanoparticles

Abstract: The chemiluminescence (CL) of bis(2,4,6-trichlorophyenyl) oxalate with hydrogen peroxide in the present of cationic surfactant and gold nanoparticles was studied. The CL emission was obviously enhanced in the presence of surfactant at a suitable concentration, with a synergetic catalysis effect exhibited. Different sizes of gold nanoparticles (15 and 50 nm) showed different effects on CL intensity. Mechanisms of the CL reaction and sensitization effect are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…After the completion of the immune response process, the chemiluminescence analysis process was based on the reaction of 3-(4-hydroxyphenyl propionate) (PHPPA) with hydrogen peroxide-urea (CH 4 N 2 O·H 2 O 2 ), catalyzed by HRP, produced fluorescence of 3-(4-hydroxyphenyl propionate) dimmer, and then, hydrogen peroxide and TCPO react and produce an active intermediate, postulated as 1,2-dioxetanedione [32], which quickly transferred energy to the fluorophore of PHPPA dimmer. Its reaction with the high energy intermediate produces the excited state product which quickly emits light.…”
Section: Optimization Of Investigation Conditionsmentioning
confidence: 99%
“…After the completion of the immune response process, the chemiluminescence analysis process was based on the reaction of 3-(4-hydroxyphenyl propionate) (PHPPA) with hydrogen peroxide-urea (CH 4 N 2 O·H 2 O 2 ), catalyzed by HRP, produced fluorescence of 3-(4-hydroxyphenyl propionate) dimmer, and then, hydrogen peroxide and TCPO react and produce an active intermediate, postulated as 1,2-dioxetanedione [32], which quickly transferred energy to the fluorophore of PHPPA dimmer. Its reaction with the high energy intermediate produces the excited state product which quickly emits light.…”
Section: Optimization Of Investigation Conditionsmentioning
confidence: 99%
“…Another simple method is the use of surfactants, which lead to changes in the microenvironments in which reactive intermediates take part in the chemiexcitation steps by interacting with the fluorophores. Several reports have dealt with the effects of surfactants on PO‐CL, and various effects of neutral, cationic and anionic surfactants on the CL efficiency have been documented , however, these results cannot be easily integrated into a simple system because surfactants behave in different ways depending on the reactants and the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the proposed CL systems in micellar media showed that enhancement on the CL intensity could arise by the solubilization of the reagents, the electrostatic effect of the ionic surfactant, and the alteration of the pH and the microenviroment of the CL reaction. 35,36 There are some studies on analytical applications for the determination of fluorophores, proteins, and hydrogen peroxide in aqueous samples using the PO-CL reaction with the introduction of the micelles. [28][29][30][37][38][39][40][41][42][43][44] Sodium dodecyl sulfate (SDS) micellar medium was used as a carrier to avoid the rapid degradation of TCPO in water in a flow-injection analysis, [28][29][30]41 allowing the use of TCPO in the absence of organic solvent.…”
Section: Introductionmentioning
confidence: 99%